The relationship between export and import towards economic growth in Malaysia / Nurul Athirah Rosli - Rosli, Nurul Athirah (2015)
This study is to analyze the relationship between export and import towards economic growth in Malaysia. The variable used to measure the economic growth in Malaysia is Gross Domestic Products. Malaysia is a developing country. Export and import are actively influenced the movement of the economic growth in Malaysia since their role as the driver in achieving the optimal growth of the country. Economic growth in Malaysia can increase by exporting more goods in order to gain foreign exchange reserves that can be used to import items that needed by country. Data on the economic growth, export and import from the year 1963 to 2012 were collected for the study purpose. The relationship between these variables is shown by using Econometric Views statistical package and the source of data used is Department Statistic of Malaysia.